Ecology of colonizing populations of the figfly Zaprionus indianus (Diptera, Drosophilidae) in Porto Alegre, Southern Brazil - Silva,Norma Machado da (2005)
Ecological parameters such as trophic niche overlap and niche breadth were computed from the frequency of all drosophilid species collected in 2001 and 2002, in the urban area of Porto Alegre city, Brazil. Independently of place, drosophilids community composition and components breeding or feeding sites, the highest frequencies of Zaprionus indianus (Gupta, 1970) were obtained during seasons with higher average temperatures, especially during summer. From a total of the 19,146 individuals of Z. indianus sampled, 80% were found in this season. The data of trophic niche breadth suggest a higher opportunism of adult flies in feeding substrate use, but the females are still selective in oviposition substrate choice. For the values of niche overlap, only for some species, did we find any correlation between these and species richness and/or number of resources, and the most of the correlation values considering breeding and feeding sites were positive. The colonization of Z. indianus in Porto Alegre could be leading to adjustments in the survival strategies of the resident species, but it is possible that many species have conditions for coexisting with the invader.